MEASURING THE SUDANESE ISLAMIC BANKS’ SCALE EFFICIENCY, TECHNOLOGICAL CHANGE AND TFP GROWTH USING TRANSLOG COST FUNCTION - Abdullah, Maziruddin; Saaid, Abd elrhman Elzahi (Tafakkur; مجلد 5 عدد 2 (2003), 2003)
not found